2008
DOI: 10.1590/s1676-06032008000400017
|View full text |Cite
|
Sign up to set email alerts
|

Frogs of Marambaia: a naturally isolated Restinga and Atlantic Forest remnant of southeastern Brazil

Abstract: Abstract:We report the results of a seven-year survey of the anurans of Marambaia, in the State of Rio de Janeiro, southeastern Brazil, where 24 species were recorded. The species represented nine families: Hylidae (10 species), Bufonidae (3), Leptodactylidae (3), Hylodidae (2), Microhylidae (2), Craugastoridae (1), Centrolenidae (1), Cycloramphidae (1), and Leiuperidae (1). We also present notes on the natural history and habitat usage by the anurans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 17 publications
4
19
0
4
Order By: Relevance
“…The richness of frog species recorded in the present study for Baixada do Maciambu is similar when compared to preliminary species lists for the restingas of Maricá (14 species) (Britto-Pereira et al 1988), Jurubatiba (10 species) and Marambaia (12 species, considered only for restinga area) (Silva et al 2008), all in the state of Rio de Janeiro. The total species richness recorded in a study comparing ten different restinga habitats in the states of Rio de Janeiro, Espírito Santo, and Bahia was 28, but considering the number of species recorded for each locality, the one with the highest richness was Praia das Neves, in the state of Espírito Santo, with 13 species (Rocha et al 2008).…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…The richness of frog species recorded in the present study for Baixada do Maciambu is similar when compared to preliminary species lists for the restingas of Maricá (14 species) (Britto-Pereira et al 1988), Jurubatiba (10 species) and Marambaia (12 species, considered only for restinga area) (Silva et al 2008), all in the state of Rio de Janeiro. The total species richness recorded in a study comparing ten different restinga habitats in the states of Rio de Janeiro, Espírito Santo, and Bahia was 28, but considering the number of species recorded for each locality, the one with the highest richness was Praia das Neves, in the state of Espírito Santo, with 13 species (Rocha et al 2008).…”
Section: Introductionsupporting
confidence: 85%
“…The greatest number of frog species recorded in restingas until now was reported from Mata São João in the state of Bahia, with 30 species (Bastazini et al 2007), followed by Parque Estadual de Itapeva, in the state of Rio Grande do Sul, with 28 species (Colombo et al 2008) and, the Juréia-Itatins Ecological Station, state of São Paulo, with 20 species (Narvaes et al 2009). In terms of species richness, the family Hylidae was the most representative in the restinga of Baixada do Maciambu (Table 1), as well as in other restinga environments in Brazil Bastazini et al 2007;Colombo et al 2008;Silva et al 2008;Narvaes et al 2009). Carvalhoe- Silva et al (2000) listed 52 frog species occurring in restingas of eastern Brazil; here we add to their list the species Dendropsophus werneri (Figure 1D), Elachistocleis bicolor ( Figure 2F), Leptodactylus gracilis ( Figure 2D), Odontophrynus maisuma ( Figure 1B), Physalaemus cuvieri ( Figure 2C), Phyllomedusa distincta (figure 1G), Scinax granulatus ( Figure 2B), and Sphaenorhynchus caramaschii, recorded by us at the Baixada do Maciambu.…”
Section: Introductionmentioning
confidence: 99%
“…Several points indicate the relevance of this island in preserving the fauna: (1) the occurrence of Vampyrodes caraccioli, only known in Atlantic Forest in Southern Bahia (Faria et al, 2006), and on this island (Bezerra et al, 2004;Peracchi and Nogueira, 2008; this work); (2) two species included in the Brazilian endangered Species List, Platyrrhinus recifinus and Lonchophylla bokermanni (Machado et al, 2005); (3) a recent survey of lizards demonstrated the occurrence of 12 species, with one endangered species, Cnemidophorus littoralis (Rocha, Araújo, Vrcibradic and Costa, 2000) (Carvalho et al, 2007) and (iv) a extensive survey confirmed 24 species of anurans, with one endemic to the island, Leptodactylus marambaiae Izecksohn, 1976 (Izecksohn andCarvalhoe-Silva, 2001) and the Ilha da Marambaia represents the southernmost limit to two species Rhinella pygmaea (Myers and Carvalho, 1952) and Xenohyla truncata (Izecksohn, 1959) (Silva et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the number of studies concerning the composition of local amphibian and reptile fauna have also increased in this period in the state of Rio de Janeiro (e.g., Rocha and Van Sluys, 2006;Carvalho et al, 2007;Carvalho-e-Silva et al, 2000;Rocha et al, 2008;Silva et al, 2008;Pontes et al, 2009;Almeida-Gomes et al, 2008. Nevertheless, more long-term studies are still necessary in order to provide enough knowledge about the herpetofaunal diversity in this state.…”
Section: Introductionmentioning
confidence: 99%